Cord blood parameters and fetal outcome in neonates with fetal distress due to meconium staining liquor- an observational study - Aafreen, Rubab; Dabral, Anjali; Panwar, Megha; Tripathi, Anshul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Meconium staining liquor (MSL) results from passage of meconium during labour and is used to diagnose fetal distress. Thick and granular meconium has been found to have a significant association with an abnormal cord pH and lactate and worst neonatal outcome. The aim of this study was to analyse and compare the mode of delivery, cord blood parameters and fetal outcomes in cases diagnosed with different degrees of meconium staining liquor. Methods: An observational study was carried out on 76 labouring patients presenting in the active stage of labour with term, singleton pregnancy with cephalic presentation diagnosed with either thin or thick MSL. The cases were followed up and compared in thin or thick MSL group for the mode of delivery (normal vaginal delivery, instrumental delivery or caesarean section), fetal cord blood parameter after birth (cord blood pH and lactate) and the neonatal outcome. Results: 39 cases were diagnosed with thin MSL. Of these, 74.4% delivered by a normal vaginal delivery. Maximum cases had normal cord blood parameters with a favourable neonatal outcome. 37 cases had thick MSL. Lower segment caesarean section (LSCS) rate was highest in this group (i.e. 48.6%). The neonatal outcomes were as follows- 24.3% had an APGAR score <7, 43.2% required assisted ventilation, 43.2% required NICU admission and 13.5% had an early neonatal death. Conclusions: Thin MSL should be closely monitored and can be followed up for normal vaginal delivery.